USING GITHUB WHEN STUDYING THE DISCIPLINE “BASES OF WEB TECHNOLOGIES” - Horchynskyi , Serghii; Horchynska, Kateryna (Professional Pedagogics, 2022)
The urgency of the article is due to find new approaches to the organization of the educational process in teaching students in the digitalization of education and modernization of information and educational environment of higher education, improvement of training of IT specialties students in disciplines related to programming and web technologies; formation of students’ skills in working with technological tools for software development.Goal: to explore the didactic possibilities of using GitHub’s version control and collaborative code hosting platform in the course of learning the discipline “Basics of Web Technologies”.Methods: theoretical (analysis of scientific sources, comparison, systematization); empirical (pedagogical observation of students, studying the experience of using the GitHub platform in the educational process).Results: the functional features of the GitHub platform were analyzed; the possibilities of its use in the process of studying the discipline “Basics of Web Technologies” were revealed (use of the full functionality of the Git version control system when interacting with GitHub; free publication of websites; convenient interaction of students and teachers when performing and checking student works; wide opportunities for performing collective works of students ; using a professional and popular tool for IT professionals).Conclusions: it was found that the GitHub platform has significant opportunities for using in the educational process: for submitting and checking student works (laboratory, individual tasks), performing collective projects (with any number of participants) in programming and web technologies, placing educational methodological materials for students.
Keywords: GitHub; using of GitHub in the educational process; tools for software development; modernization of the information and educational environment of a higher education institution; methods of teaching students programming and web technologies